2012
DOI: 10.4292/wjgpt.v3.i6.83
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants can treat inflammatory bowel disease through regulation of the nuclear factor-κB/nitric oxide pathway and inhibition of cytokine production: A hypothesis

Abstract: Inflammatory bowel disease (IBD) is a group of inflammatory disorders mainly affecting the colon and small intestine. The main types of IBD are Crohn's disease (CD) and ulcerative colitis (UC). UC is restricted to the large intestine whereas CD can affect any part of the gastrointestinal tract. Treating this disorder depends on the form and level of severity. Common treatment involves an anti-inflammatory drug, such as mesalazine, and an immunosuppressant, such as prednisone. Several signaling pathways, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…Based on these studies, the NF-κB pathway has been considered to play an important role in the inflammatory process. Therefore, investigators have hypothesized that the antidepressant-like effects of amitriptyline, via the modulation of this pathway, may be more effective for treating and suppressing the development of IBD through its anti-inflammatory actions [67] . Some authors have argued that antidepressants may, in fact, cause tolerance and present problems when tapering off medications [68,69] .…”
Section: Psychiatric Therapy In Ibdmentioning
confidence: 99%
“…Based on these studies, the NF-κB pathway has been considered to play an important role in the inflammatory process. Therefore, investigators have hypothesized that the antidepressant-like effects of amitriptyline, via the modulation of this pathway, may be more effective for treating and suppressing the development of IBD through its anti-inflammatory actions [67] . Some authors have argued that antidepressants may, in fact, cause tolerance and present problems when tapering off medications [68,69] .…”
Section: Psychiatric Therapy In Ibdmentioning
confidence: 99%
“…There are limitations to the extent to which conclusions can be drawn based on the reviewed studies. Many studies had small sample sizes, were not adequately powered, or were qualitative or retrospective in nature [47,66]. In addition, some studies lacked control groups, follow up measurements, or objective markers of inflammation [5].…”
Section: Resultsmentioning
confidence: 99%
“…In a study investigating the opinions and attitudes of 18 gastroenterologists towards usage of antidepressants by IBD patients, the majority thought that antidepressants did not alter the course of IBD, but did improve patient's QoL [42]. However, it has been found that antidepressants improve mental status while also decreasing inflammation through the NF-kB pathway, in addition to their effect on pro-inflammatory cytokines [3,66,67]. 15 out of 15 IBD patients (100%) taking antidepressants believe it improved their QoL, mainly seen by a reduction in anxiety, anxious mood, stress, and an increase in the ability to relax (10 patients) [67].…”
Section: Antidepressantsmentioning
confidence: 99%
“…4 Others have demonstrated a high prevalence of functional gastrointestinal disorders (FGiDs) in patients with IBD, 5 and believe that improvement in these functional bowel symptoms may be responsible for the benefit seen with these pharmacological agents. 6 However, more recent studies have demonstrated an anti-inflammatory effect at the cellular/molecular level with both tricyclic anti-depressants 7 and SSRIs. 8 Mouse models support a role for depression in altering immune mechanisms and subsequent colitis, 9 with clues as to the molecular mechanisms beginning to be elucidated.…”
mentioning
confidence: 99%